Economic Implications of Economic Corruption - النجار, يحيى غني (Journal of Economics and Administrative Sciences, 2009)
There are  many  economic issues that  concern society at the local and international levels and which constitute  a serious  challenge to the societies  and governments , perhaps  including  the issue of corruption  in all its  forms and manifestations and effects , which  now attract the attention  the issue of human society everywhere .                                                        The  term "corruption " was not known in the literature or the media before the final quarter of last century, but  spread widely and its  negative made it impose  itself  strongly in  global forums , and that started the last decade of the last century  until  the issue  of corruption became the focus attention of researchers who studied  forms of corruption.                                                      Many of the studies discussed  the issue of corruption has focused  on non-economic  reasons  for corruption, and suggested  means of reducing  corruption  through a package of laws and anti-corruption legislation and the application systems of good governance , either for reasons of economic corruption have been the lowest  share of research and analysis. Despite  the importance  of non-economic  causes  of corruption , but the economic  causes  of great importance established by the facts in the form of slower economic growth and  the erosion of  available  resources  and deepening poverty situation , which  requires due attention to this  aspect. Thus , this research focus  on the economic  effects of corruption through  disclosure  of the nature of corruption  and clarify concepts  and factors  of the spread  and the impact  on economics  variables.